Co-teaching as a model for scholarly interactions and the acceptance of limits to knowledge - Richter, Christoph; Dubroy-McArdle, Céline; Cowan, Mairi (Frontiers in Education, 2025)
Co-teaching has been shown to be an effective instructional tool in a range of academic settings. In this contribution, we are extending the list of benefits. Using quantitative and qualitative approaches, we assessed the impact of a co-taught, interdisciplinary course on students' perception of their own role as scholars, and on how students interact with their peers and their instructors in the classroom. Students clearly perceived and appreciated the benefits of having two professors from two different disciplines teaching an interdisciplinary course. They also paid close attention to the interaction between the instructors, noting that they rarely see scholars question or correct each other. Students recognized that there are limits to any scholar's knowledge, and that it is normal for researchers to ask questions of one another. Importantly, they came to see interactions between co-teachers as a model for their own role and behavior as scholars, and they took an acceptance of limits to knowledge with them beyond this one co-taught course.